2020
DOI: 10.1111/1471-0528.16217
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B infection and the risk of gestational diabetes: a cross‐sectional study

Abstract: Objective An estimated two billion people worldwide live with hepatitis B virus (HBV) infection. Many of these are women of reproductive age. Studies that have examined pregnancy outcomes in women living with HBV have reported conflicting results in relation to the incidence of gestational diabetes (GDM). The aim of this study is to examine if gestational diabetes is more common in women with chronic HBV residing in a non-Asian country. Design Cross-sectional study. Setting Victoria, Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
(52 reference statements)
0
15
1
Order By: Relevance
“…Similarly, two different studies investigating the effect of HBV infection during pregnancy suggested that HBV infection represents a significant general risk for the development of GDM 59 . Contrasting results can be seen in another meta‐analysis by Kong et al.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, two different studies investigating the effect of HBV infection during pregnancy suggested that HBV infection represents a significant general risk for the development of GDM 59 . Contrasting results can be seen in another meta‐analysis by Kong et al.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have reported an increased risk of GDM in pregnant women who are HBsAg carrier. For example, Giles et al showed that HBV was associated with GDM with a risk ratio of 1.750 for GDM (95% CI 1.600-1.900) [31]. The highest incidence (37.10%) of GDM was observed in women with HBV and a body mass index of >40 Kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…HERC5 gene expression is regulated by a variety of stimuli, particularly inflammatory factors (e.g., interferon, lipopolysaccharide (LPS), tumor necrosis factor α (TNF α ), and interleukin 1 β (IL-1 β) ) [ 51 ]. Several previous studies have shown that the incidence of GDM in pregnant women with chronic hepatitis B virus (HBV) infection is higher than that in the general population [ 52 , 53 ]. HBV infection may have an impact on glucose homeostasis and IR [ 54 ].…”
Section: Discussionmentioning
confidence: 99%